Decreased levels of dehydroepiandrosterone sulphate in severe critical illness: a sign of exhausted adrenal reserve? - Beishuizen, Albertus (BioMed Central, 2002)
INTRODUCTION: Dehydroepiandrosterone (DHEA) and its sulphate (DHEAS) are pleiotropic adrenal hormones with immunostimulating and antiglucocorticoid effects. The present study was conducted to evaluate the time course of DHEAS levels in critically ill patients and to study their association with the hypothalamic–pituitary–adrenal axis. MATERIALS AND METHOD: This was a prospective observational clinical and laboratory study, including 30 patients with septic shock, eight patients with multiple trauma, and 40 age- and sex-matched control patients. We took serial measurements of blood concentrations of DHEAS, cortisol, tumour necrosis factor-α and IL-6, and of adrenocorticotrophic hormone immunoreactivity over 14 days or until discharge/death. RESULTS: On admission, DHEAS was extremely low in septic shock (1.2 ± 0.8 mol/l) in comparison with multiple trauma patients (2.4 ± 0.5 μmol/l; P < 0.05) and control patients (4.2 ± 1.8; P < 0.01). DHEAS had a significant (P < 0.01) negative correlation with age, IL-6 and Acute Physiology and Chronic Health Evaluation II scores in both patient groups. Only during the acute phase did DHEAS negatively correlate with dopamine. Nonsurvivors of septic shock (n = 11) had lower DHEAS levels (0.4 ± 0.3 μmol/l) than did survivors (1.7 ± 1.1 μmol/l; P < 0.01). The time course of DHEAS exhibited a persistent depletion during follow up, whereas cortisol levels were increased at all time points. CONCLUSION: We identified extremely low DHEAS levels in septic shock and, to a lesser degree, in multiple trauma patients as compared with those of age- and sex-matched control patients. There appeared to be a dissociation between DHEAS (decreased) and cortisol (increased) levels, which changed only slightly over time. Nonsurvivors of sepsis and patients with relative adrenal insufficiency had the lowest DHEAS values, suggesting that DHEAS might be a prognostic marker and a sign of exhausted adrenal reserve in critical illness.